Molecular screening of Coloured South African breast cancer patients for the presence of BRCA mutations using high resolution melting analysis - Oosthuizen, Jaco (University of the Free State, 2016)
The populations of South Africa (SA) exhibit a rainbow of genetic diversity due to the high contribution of ancestral genetic admixture. The economic structure of this third world country has limited the exploration of this genetic diversity with regards to familial breast cancer (BC) testing. As the SA Coloured woman has a lifetime risk of 1 in 22 to develop BC, the main aim of the study involved targeting the highly penetrant genes BRCA1 and BRCA2 for comprehensive mutation analysis. This was done in order to determine the range of variants and mutations present within BC patients representing this group. In order to perform such a comprehensive screen, High Resolution Melting Analysis (HRMA) was optimised and validated for use in conjunction with the protein truncation test (PTT), genotyping assays using real-time based PCR, single stranded conformational analysis (SSCP) and DNA Sanger sequencing to determine the presence of potential disease-causing mutations. A total of 229 Coloured BC patients were included based on a specific selection criteria. This criteria included being affected with BC and either having a positive family history of the disease, or an early age at onset (<45 years) or bilateral disease. All male BC patients were included. Twelve different pathogenic or class 5 mutations were detected for a total of 33 patients. These mutations were identified using genotyping analysis, PTT and HRMA. These mutations were confirmed using Sanger sequencing. These mutations included all three the Afrikaner founder mutations, together with the Xhosa/Coloured mutation detected for the Xhosa and Coloured population residing in the Western Cape. A total of 50 variants were identified using HRMA, ranging from single base changes to a 12bp deletion occurring within the coding region of BRCA2. The clinical significance of these variants were classified using computer-based analysis. Variants of unknown significance (VUS) were investigated using a multiple evidence-based approach in order to confirm their clinical status. These included using the BIC, ClinVar, the ENIGMA guidelines, and the 1000 Genomes project database. This was done in order to investigate whether the variant was novel or allocated to a specific population cluster. The majority of the variants was class 1 polymorphisms, exhibiting normal variation. The portfolio of variants reflected 300 years of admixture between the Bantu-speaking Black African populations of the North Western Cape province, the European settlers and the slaves from the East as global, Eastern and African polymorphisms were observed. Numerous new pathogenic mutations were identified, ranging from likely pathogenic (class 4) to class 5. Many of these mutations proved to be restricted to the southern tip of SA. Based on these results, recommendations can be made regarding the composition of targeted mutation panels for the diagnostic testing of SAC BC patients and their families.

Die bevolking van Suid-Afrika (SA) beskik oor ’n reënboog van genetiese diversiteit wat te wyte is aan die hoë bydrae van voorvaderlike genetiese vermenging. Die ekonomiese struktuur van hierdie derdewêreldse land het die ontginning van hierdie diversiteit met betrekking tot oorerflike borskankertoetsing verhinder. Die hoofdoelwit van die studie was om hierdie twee hoë-impak borskankergene te analiseer in Kleurlingpasiënte, aangesien hulle risiko vir die ontwikkeling van die siekte 1 uit elke 22 is. Hierdie studie is nodig om die tipe en verskeidenheid van mutasies te bepaal wat moontlik teenwoordig kan wees by Kleurling borskankerpasiënte. Ten einde so ’n omvattende analise uit te voer, is die nuwe mutasie siftingstegniek, High Resolution Melting Analysis (HRMA), geoptimiseer en gevalideer vir gebruik. In samewerking met die Protein Truncation Test (PTT), genotipering met behulp van qPCR, enkelstring konformasie-ontleding (SSCP) en DNA volgordebepaling kon hierdie ontledings gedoen word. ŉ Totaal van 229 Kleurlingpasiënte is ingesluit op grond van spesifieke kriteria. Die kriteria is gebaseer op die teenwoordigheid van ŉ positiewe familiegeskiedenis, of ŉ vroeë ouderdom van diagnose (<45 jaar) of bilaterale aantasting. Alle geaffekteerde mans is ingesluit. Twaalf verskillende siekte-veroorsakende of klas 5 mutasies is geïdentifiseer vir ŉ totaal van 33 pasiënte. Hierdie mutasies is geïdentifiseer met behulp van genotipering, PTT en HRMA en is bevestig deur middel van DNA volgordebepaling. Al drie die Afrikaner stigtersmutasies sowel as die herhalende Kleurling- of Xhosamutasie is geïdentifiseer vir hierdie bevolking woonagtig in die Wes Kaap. ’n Totaal van 50 verskillende variante is geïdentifiseer deur gebruik te maak van HRMA. Hierdie variante het gewissel van enkelbasisveranderinge tot ŉ 12 basis paar delesie teenwoordig in ekson 10 van BRCA2. Die kliniese belang van hierdie variante is bepaal deur gebruik te maak van rekenaaranalises. Variante waarvan die kliniese impak onseker was, is addisioneel ondersoek deur gebruik te maak van verskeie databasisse wat gebaseer was op konkrete bewyse. Hierdie databasisse het die volgende ingesluit, naamlik die BIC, ClinVar, die riglyne van ENIGMA en die 1000 Genoomprojek. Hierdie addisionele studies was nodig om te bepaal of die variant nuut was of reeds in ’n spesifieke bevolkingsgroep voorgekom het. Die meerderheid van die variante was verteenwoordigend van gewone polimorfismes. Die versameling variante het 300 jaar se vermenging tussen die Bantoe-sprekende swart bevolkings van Afrika, die Europese setlaars en die slawe uit die Ooste versinnebeeld, aangesien die polimorfismes geïdentifiseer verteenwoordigend van die wêreld, die Ooste en Afrika was. Verskeie nuwe siekte-veroorsakende mutasies is geïdentifiseer wat gevarieer het tussen klas 4 en klas 5. Baie van hierdie mutasies was beperk tot die suidelike gedeelte van Suider-Afrika. Aanbevelings vir die samestelling van spesifieke mutasiepanele vir die diagnostiese toetsing van SA Kleurlingpasiënte en hulle familielede kan gemaak word, gebaseer op die resultate van hierdie studie.
Dissertation (M.Med.Sc. (Human Genetics))--University of the Free State, 2016
Keywords: South Africa; BRCA1/2; HRMA; Mutation screening; Computer-based analysis; Coloured population; Breast -- Cancer; Breast -- Cancer -- Genetic aspects